Validation of the completeness and accuracy of the Northern Ireland Cancer Registry. Issue 3 (June 2015) - Kearney, T.M.; Donnelly, C.; Kelly, J.M.; O'Callaghan, E.P.; Fox, C.R.; Gavin, A.T.
Highlights: Completeness and accuracy of data held within cancer registries has been questioned. NI Cancer Registry compared their database with general practitioner data. 17, 102 cancer patient records were compared finding a registry completeness of 99.9%. Only 0.08% of GP patients ( n  =  15) were not included in registry records. This study confirms the credibility of Northern Ireland Cancer Registry data. Abstract: Background: It has been suggested that inaccuracies in cancer registries are distorting UK survival statistics. This study compared the Northern Ireland Cancer Registry (NICR) database of living patients, with independent data held by Northern Ireland's General Practitioners (GPs) to compare and validate the recorded diagnoses and dates held by the registry. Methods: All 387 GP practice managers were invited to participate. 100 practices (25.84%) responded. Comparisons were made for 17, 102 patients, equivalent to 29.08% of the living patients (58, 798) extracted from the NICR between 1993 and 2010. Results: There were no significant differences ( p  > 0.05) between the responding and nonresponding GP patient profiles for age, marital status or deprivation score. However, the responding GPs included more female patients ( p  = 0.02). NICR data accuracy was high, 0.08% of GP cancer patients ( n  = 15) were not included in registry records and 0.02% ( n  = 2) had a diagnosis date which varied more than 2 weeks from GP records (3 weeks and 5 months). The NICR had recorded two different tumour types and three different tumour statuses (benign vs. malignant) to the GPs. Conclusion: This comparison demonstrates a high level of accuracy within the NICR and that the survival statistics based on this data can be relied upon.